Descriptions of two new leafhopper species of the genus Flaviata Lu & Qin (Hemiptera, Cicadellidae, Typhlocybinae) from Southern China, with a key to known species - Xu, Ye; Lu, Sihan; Dietrich, Christopher H.; Qin, Daozheng (Zootaxa, 2018)
Two new species of the empoascine leafhopper genus Flaviata, F. furcata Xu, Lu & Qin, sp. n. and F. sinuata Xu, Dietrich & Qin, sp. n., are described from southern China. Habitus photos and illustrations of male genitalia and a key to the known species of the genus, based on male genitalia, are also provided.